2020
DOI: 10.1002/ffj.3623
|View full text |Cite
|
Sign up to set email alerts
|

Aroma absorption in rapeseed oil using rotating packed bed

Abstract: An increasing consumers’ call for natural aromas fuels the development of biotechnological aroma production. Although aroma fermentation is quite advantageous, especially severe product losses of volatile compounds through the bioreactor off‐gas may challenge the downstream processing. The application of novel process intensification methods to overcome the common drawbacks of conventional apparatuses might be helpful on a way to commercial competitiveness of biotechnological aromas. This study explored the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, adding packing material lowers the rotational speed at which the maximum separation efficiency is reached. These results can be supported by the investigations reported by Lukin et al 25 that the total wetted surface area of the empty rotor (without packing) and the casing is approximately in the range of 69−88% of the surface area generated in an RPB when the packing is used. 25 Therefore, it appears that the available conventional RPB packings need to be further improved to efficiently utilize their high specific surface areas efficiently.…”
Section: Contribution Of Packing and Casing To The Overall Mass Trans...supporting
confidence: 82%
See 3 more Smart Citations
“…However, adding packing material lowers the rotational speed at which the maximum separation efficiency is reached. These results can be supported by the investigations reported by Lukin et al 25 that the total wetted surface area of the empty rotor (without packing) and the casing is approximately in the range of 69−88% of the surface area generated in an RPB when the packing is used. 25 Therefore, it appears that the available conventional RPB packings need to be further improved to efficiently utilize their high specific surface areas efficiently.…”
Section: Contribution Of Packing and Casing To The Overall Mass Trans...supporting
confidence: 82%
“…Nevertheless, the results of the current research can be supported by experiments on ethanol dehydration conducted by Qammar et al , using a metal foam with varying outer radii as well as with an empty rotor having the same F -factor and RPB design as in the current study. They showed that even with no packing, there is a certain amount of separation in an RPB, which leads to the observation that there might not be a significant contribution of the end-zone to the overall mass transfer; instead, it might be the result of mass transfer on empty rotor plates and the mass transfer in the casing as also supported by the wetted area observations made by Lukin et al in an RPB (height to packing radius = 0.2) with and without packing. Table indicates that almost half of the separation is achieved even with no packing compared to the separation with a packing length of 0.19 m. If a few centimeters of the packing is added to the empty rotor, then it only increases the Nth by half a stage, and so on.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations